Tension attributes of the family caregiver of frail older adults - Fernandes, Maria das Graças Melo; Garcia, Telma Ribeiro (Revista da Escola de Enfermagem da USP, 2009)
The objective of this study was to assess both theoretically and empirically the tension attributes of the family caregiver of frail older adults. The theoretical phase consisted of analyzing 52 studies addressing this issue. The analysis showed that the phenomenon is evidenced by the caregiver through physical and emotional changes, unbalance between activity and rest, and compromised individual coping. In the field phase, an assessment was made of 30 women who, during the nursing consultation, showed evidence of tension due to their role as caregiver. Data collection was performed through interviews at home, which were recorded and followed a script created based on the theoretical findings. Every time it was considered adequate, excerpts from the caregivers' discourses were added to improve understanding. The empirical assessment confirmed the tension attributes revealed in the theoretical analysis.